Impact of dentists and equipment in the performing dental imaging examinations: a longitudinal analysis - Danielle Bianca de Lima Freire; Roger Keller Celeste; Mariana Boessio Vizzotto; Luciana Neves Nunes; Nádia Assein Arús; Heraldo Luís Dias da Silveira (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: In this study, we aimed to identify factors associated with performing dental imaging examinations in public health services. Brazilian data at the municipal level (n = 5,564) in two time periods, P0 (2005-2007) and P1 (2014-2016), were collated from health information systems. The increase in the municipal rates of intraoral and extraoral radiographic imaging procedures was the outcome. Changes in the use of clinical procedures and the rates of dentists and equipment were the main predictors. Multiple logistic regression analysis was performed to estimate the adjusted odds ratio (OR). Approximately 35.3% of the Brazilian municipalities increased the dental radiography equipment rate, 9.9% increased the fan-beam computed tomography (CT) equipment rate, and 5.9% increased the magnetic resonance imaging (MRI) equipment rate. In addition, 31.8% increased the periapical/interproximal radiography rate, 10.5% increased the CT rate, and 4.4% increased the MRI rate. Increases in the dental radiography, CT, and MRI rates were associated with higher chances of periapical/interproximal images (OR = 1.90, p < 0.01), face and neck images (OR =1 5.3, p < 0.01), and MR images (OR = 18.1, p < 0.01), respectively. Municipalities that increased the rates of endodontists increased the rates of periapical/interproximal (OR = 2.50, p < 0.01) and occlusal (OR = 1.60, p < 0.01) imaging procedures, and those that increased the rates of radiologists also increased the rates of occlusal (OR = 2.00, p < 0.01) and panoramic (OR = 1.70, p < 0.01) imaging procedures. The implementation of a secondary dental care center, Centro de Especialidades Odontológicas (CEO) was associated with an increase in the chances of performing periapical/interproximal and panoramic radiographic procedures in 1.5 and occlusal radiographic examinations in 2.0. The rates of dentists, equipment, specialized dental centers, and specific dental procedures were associated with the increased use of imaging procedures in dentistry in the Brazilian public health system.